Influence of micro-pits on sliding motion under low speeds for block-on-disk tribotester. (1st November 2016) - Nuraliza, N.; Syahrullail, S.; Razak, D. M.; Azwadi, C. S. N.
ABSTRACT: The tribological behaviour of surface texture with embedded pits or dimples using pin on disk with modification from point contact (original pin-on-disk specification) to surface contact under lubricated sliding motion is investigated. A series of experimental results are presented to evaluate the effect of dimples at low sliding speed. Load, spacing of pits, and number of pits are varied to explore their influence on the friction mechanism. It shown that with proper dimensions of dimples, the friction performance of surface texture can be improved due to pit characteristics. The results reveal that surface texture without pits does not reduce tribological problems compared to surface with embedded pits. Furthermore, experimental results also indicate that surface textures with pits have large distance and show better frictional performance and wear rate value with close pits.